2021
DOI: 10.1371/journal.pone.0255514
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Cannabis and opioid use disorder among heart failure admissions, 2008–2018

Abstract: Background In the United States, both cannabis use disorder (CUD) and opioid use disorder (OUD) have increased in prevalence. The prevalence, demographics, and costs of CUD and OUD are not well known in heart failure (HF) admissions. This study aimed to use a national database to examine the prevalence, demographics, and costs associated with CUD and OUD in HF. Methods This study used the National Inpatient Sample from 2008 to 2018 to identify all primary HF admissions with and without the co-diagnosis of OU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…7 Between 2008 and 2018, a total of 67 137 individuals with OUD were diagnosed with heart failure out of the 11 692 995 heart failure admissions identified in the general population. 8 A study on OUD and myocardial infarction (MI) showed that the prevalence of individuals with OUD experiencing MI doubled from 2006 to 2015, increasing from 163 to 326 cases per 100 000. 9 In terms of general cardiovascular mortality, research with participants aged 40 to 75 years found long-term opiate use was associated with increased cardiovascular mortality, independent of the traditional risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…7 Between 2008 and 2018, a total of 67 137 individuals with OUD were diagnosed with heart failure out of the 11 692 995 heart failure admissions identified in the general population. 8 A study on OUD and myocardial infarction (MI) showed that the prevalence of individuals with OUD experiencing MI doubled from 2006 to 2015, increasing from 163 to 326 cases per 100 000. 9 In terms of general cardiovascular mortality, research with participants aged 40 to 75 years found long-term opiate use was associated with increased cardiovascular mortality, independent of the traditional risk factors.…”
Section: Introductionmentioning
confidence: 99%